2012
DOI: 10.1590/s1516-18462012005000032
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre voz, autoavaliação vocal e qualidade de vida em voz de professoras

Abstract: OBJETIVO: avaliar a qualidade vocal, autoavaliação e a qualidade de vida em voz em professoras do ensino fundamental do 1º ao 5º ano e correlacionar os achados. MÉTODO: estudo transversal observacional de correlação, com 73 professoras do ensino fundamental do 1º ao 5º ano de escolas públicas da Rede Estadual de Educação de Maceió/AL. Aplicou-se um questionário inicial no qual continha uma pergunta de autoavaliação, posteriormente as vozes foram gravadas para análise perceptivo-auditiva por meio da escala anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
2
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 25 publications
(55 reference statements)
8
34
2
8
Order By: Relevance
“…In the present study, the studied group was characterized by a predominance of females, adult, no professional use of voice and individuals with FD, agreeing with other current studies found in the literature 13,14 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, the studied group was characterized by a predominance of females, adult, no professional use of voice and individuals with FD, agreeing with other current studies found in the literature 13,14 .…”
Section: Discussionsupporting
confidence: 93%
“…According to the literature, the age variable deserves attention, because as age advance, the vocal efficiency decreases, with greater or lesser vocal impact 13 , and a positive correlation was found between the total score of VHI and age 19 . Other studies have also found that elderly showed lower scores of V-RQOL compared to younger individuals, realizing greater impact of dysphony on their quality of life 23,24 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations